(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
This paper presents a new system to manage traffic in a high congested area. The IoT technology is utilized for traffic management and identification of defaulters. The raspberry-pi, RFID, and IR sensors are used to implement the system. The proposed system is incorporated with decisive and round-robin algorithm to detect the optimal path to further indicate the direction for traffic. IR sensors regulates the density of traffic in an area by RFID. The traffic signals connected with cameras in metro cities cab be upgrade by connecting to IoT. This system is very useful during the pandemic. The police can easily control the traffic from mobile phone from their home and identify the defaulters also. The proposed system helps in sequestering of ambulance, firefighting vehicles from daily traffic. There is an extra benefit of using RFID that supports in locating the robbed or snatched vehicles.